Adequacy of micromineral content (Fe, Zn, Cu) of Napier grass (Pennisetum purpureum) as beef cattle feed in Merapi volcanic slopes of Magelang Regency, Indonesia: Kecukupan kandungan mikromineral (Fe, Zn, Cu) rumput gajah (Pennisetum purpureum) sebagai pakan ternak sapi pedaging di pegunungan Merapi di Kabupaten Magelang, Indonesia - Hartati, L; F Syarifudin, F Syarifudin; P B Pramono, P B Pramono; Hidayah, Nur; D Suhendra, D Suhendra; M Arifin, M Arifin (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
A study was conducted to assess the micromineral content of Pennisetum purpureum, commonly known as Napier grass, in the Magelang Regency of Central Java, Indonesia. Three different topographical areas, namely flat, undulated, and sloping, were considered for the study. Samples of Napier grass were collected from each area, with a total of 20 samples taken from each area. The samples were then subjected to various processing techniques, including fresh weight measurement, chopping, sun-drying, oven-drying, and milling. The mineral content of the samples was determined using an atomic absorption spectrophotometer (AAS). The results revealed that the mineral content of Zn and Cu in Napier grass varied significantly across the three topographical areas (p<0.05), with average values of 40.34 and 11.56 ppm, 33.44 and 10.75 ppm, and 40.38 and 13.43 ppm for flat, undulated, and sloping areas, respectively. The Fe content, on the other hand, was found to be not significantly different across the areas, with an average of 377.90 ppm. These findings suggest that the use of Napier grass as a basal feed for beef cattle, with a dry matter requirement of 7.56 kg day-1 and a proportion of Napier grass of 7.13 kg DM day-1, would provide sufficient micro minerals, including Fe, Cu, and Zn, for the cattle in the three topographical areas. Key words: mineral, napier grass, topography